Strategi Pengembangan Wisata Relegi Desa Kuncen Untuk Peningkatan Ekonomi Masyarakat - Radi Istiyanto; Fadly Usman; Abdul Wahid Hasyim (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2025)
Tourism has been recognized as a highly significant sector for economic growth and social progress in many regions worldwide. The religious tourism area of the Minak Anggrung tomb in Kuncen Village, Padangan District, is one of the efforts by the local government of Bojonegoro Regency to develop. However, the management of the Minak Anggrung religious tourism area is still not optimal due to insufficient facilities and infrastructure. The objective of this research is to determine and analyze the development strategies for the Minak Anggrung tomb tourism. Informants in this research are determined using the snowball sampling technique. The analysis method used is SWOT analysis by analyzing the strengths, weaknesses, opportunities, and threats of the Minak Anggrung tomb tourism area. The results of this research indicate that many development strategies need to be implemented. These include strategies for developing religious tourism destinations, human resource development, infrastructure development, institutional development, and targeted promotional strategies. It is hoped that the implementation of these development strategies can lead to positive changes, thus increasing tourist visits and consequently improving the local economy.